Peningkatan Kemampuan Mengemukakan Pendapat Melalui Metode Demonstrasi Kelas II di SDN Sungai Raya Kabupaten Raya - Rahmaniar, Neneng; Yuniarti; Herawati (Indonesian Journal Publisher, 2024)
In general, students have a high curiosity about the knowledge that has been given by the teacher in a learning process, but only some students dare or are able to express their opinions in asking questions or giving responses. This study aims to plan, implement and describe the evaluation of the learning outcomes of the demonstration method of the ability to express opinions at SDN 27 Sungai Raya Kubu Raya. The method used in this study is descriptive qualitative. The results of this study on the ability to express opinions in Cycle 1 showed that 79.16% of children were in the category of Not Yet Brave (BB) and 50% of children were Starting to Brave (SSB). In Cycle II, 58.33% were in the category of Not Yet Brave (BB), and 89.67% were in the category of Already Brave (SSB). In Cycle III, the remaining 16.6% were in the category of Not Yet Brave (BB), and 125% were Starting to Brave (SSB). Based on the results of this study, there was an increase in the level of Already Brave (SMB) according to the achievement indicators, but the level of Already Very Brave (SSB) had not yet increased. This is likely due to insufficient time and the unavailability of facilities and infrastructure that can support the learning activities to take place properly.